Human-Centered Innovation in Language Learning: Overcoming Business Model Stagnation through Market Pull and Design Thinking - Safira Maulidina (Green Publisher Indonesia, 2026)
This study explores how a small language-learning business in Indonesia can overcome growth stagnation by implementing a human-centred approach to innovation. Adopting the Design Thinking framework as the primary methodological lens, the research explores learner expectations, challenges and preferred learning formats, with the objective of improving products and business models. Data were collected through focus group discussions (FGDs) involving six learner groups that were identified during the early exploratory phase. Braun and Clarke’s thematic analysis was used to analyze the qualitative data and uncover recurrent needs related to motivation, confidence, learning structure, flexibility and the role of human support. These insights were then used to create two core personas representing the two main learner types. These personas then guided the development of five 'How Might We' (HMW) questions, which acted as drivers for the ideation process. The study resulted in three integrated low-fidelity prototypes: (1) modular learning pathways, (2) an adaptive weekly roadmap, and (3) a simple confidence progress tracker. These elements form a coherent learning ecosystem, designed to improve learner engagement and strengthen business sustainability by offering clearer value, better retention and more structured products. The findings indicate that designing products to align with learner expectations can support the long-term sustainability of small EdTech startups. The study recommends conducting future quantitative tests on the proposed prototypes to evaluate their expected usefulness and acceptance among a wider range of learners.